Proceedings of the 5th International Conference on Food, Agriculture and Natural Resources (FANRes 2019) 2020
DOI: 10.2991/aer.k.200325.050
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rainfall Harvesting as a Fertigation Resources Using Autopot on Quality of Melon (Cucumis melo L.)

Abstract: Global climate changes which cause increasing the dry season and impact of decreasing in water resources. Water has an important role in agriculture sector especialy to the process of plant growth and water use efficiency while rainfall harvesting will impact of water quality .Fertigation and using autopot is an alternative of water used efficiency and plant nutrition. Fertigation also will affect the ability of melon (Cucumis melo L) to produce quality of melon especially water use efficiency, carbohydrate, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
0
5
0
1
Order By: Relevance
“…III showed that water 95.19%; fat 0.88%; ash 0.57%; protein 1.37%; carbohydrate 1.99%; vitamin C 6.91% and sweeteners 9.4% 0Brix. When compared to research [9] data, that water in melon good on 93%; it means soil water irrigation good enough as irrigation resources for melon quality. The other parameters, for example, ash; melon is a good quality when ash 0.45%, while research results are 0.57%.…”
Section: B the Quality Of Melonmentioning
confidence: 88%
See 3 more Smart Citations
“…III showed that water 95.19%; fat 0.88%; ash 0.57%; protein 1.37%; carbohydrate 1.99%; vitamin C 6.91% and sweeteners 9.4% 0Brix. When compared to research [9] data, that water in melon good on 93%; it means soil water irrigation good enough as irrigation resources for melon quality. The other parameters, for example, ash; melon is a good quality when ash 0.45%, while research results are 0.57%.…”
Section: B the Quality Of Melonmentioning
confidence: 88%
“…The research was carried out at the greenhouse located in Universitas Padjadjaran campus, Jatinangor Sumedang, West Java Province, Indonesia; is on 6'48'LS and 107'21' BT with an elevation of 753,96 m a.s.l with an average temperature 18-30 o C and humidity of 85 93% The research method is descriptive analysis, i.e., analyzing data quantitatively and investigating the link between the soil water qualities on consumptive water use; soil water qualities and melon's qualities were melon planted in on the autopot with growth media uses mixed of charcoal husk combined with zeolite with ratio 9:1 and 15 cm height [7] Soil water used to collect from the soil and stored to a water tank or in the big torrents, which each torrent content 5300 litres and in this research, had four torrents available. From big torrents, soil water delivered into small torrents in the greenhouse and combined with mineral nutrient or called fertigation and the end of irrigation supplying to melon crops with growth in autopot through at the small pipe [5].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Menurut Bafdal et al (2019) kelangkaan air dapat terjadi karena ketidakmampuan tanaman untuk mengakses air yang ada karena keterbatasan prasarana dan teknologi. Oleh karena itu perlu adanya teknologi untuk memudahkan pengoperasian pintu air irigasi, salah satunya adalah otomasi pengoperasian pintu air irigasi dengan mikrokontroler.…”
Section: Pendahuluanunclassified